2013
DOI: 10.1371/journal.pone.0077689
|View full text |Cite
|
Sign up to set email alerts
|

The Oxytocin Receptor Gene (OXTR) in Relation to State Levels of Loneliness in Adolescence: Evidence for Micro-Level Gene-Environment Interactions

Abstract: Previous research has shown that the rs53576 variant of the oxytocin receptor gene (OXTR) is associated with trait levels of loneliness, but results are inconsistent. The aim of the present study is to examine micro-level effects of the OXTR rs53576 variant on state levels of loneliness in early adolescents. In addition, gene-environment interactions are examined between this OXTR variant and positive and negative perceptions of company. Data were collected in 278 adolescents (58% girls), by means of the Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 32 publications
1
28
1
Order By: Relevance
“…We did not identify any genome-wide significant associations (Figure 1 and Supplementary Figures S4-S6), presumably reflecting the very modest contributions of individual variants. Previous studies have reported associations between polymorphisms in a handful of candidate genes and loneliness (Chou, 2010;Chou et al, 2014;Connelly et al, 2014;Lan et al, 2012;Lucht et al, 2009;Terracciano et al, 2010;Tsai et al, 2012;van Roekel et al, 2010van Roekel et al, , 2011van Roekel et al, , 2013Verhagen et al, 2014;Wang et al, 2013); our study did not provide even nominal evidence for replication, despite our much larger sample size (Table 2). Finally, we identified varying levels of evidence for coheritability between personality traits (positive for neuroticism and negative for extraversion) and psychiatric disease traits (negative for schizophrenia and bipolar disorder and positive for depression).…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…We did not identify any genome-wide significant associations (Figure 1 and Supplementary Figures S4-S6), presumably reflecting the very modest contributions of individual variants. Previous studies have reported associations between polymorphisms in a handful of candidate genes and loneliness (Chou, 2010;Chou et al, 2014;Connelly et al, 2014;Lan et al, 2012;Lucht et al, 2009;Terracciano et al, 2010;Tsai et al, 2012;van Roekel et al, 2010van Roekel et al, , 2011van Roekel et al, , 2013Verhagen et al, 2014;Wang et al, 2013); our study did not provide even nominal evidence for replication, despite our much larger sample size (Table 2). Finally, we identified varying levels of evidence for coheritability between personality traits (positive for neuroticism and negative for extraversion) and psychiatric disease traits (negative for schizophrenia and bipolar disorder and positive for depression).…”
Section: Discussioncontrasting
confidence: 70%
“…Although our findings cast doubt on the previously reported associations-or at least on the original effect sizes that were identified-there are potentially important differences between our study design and the previously published candidate gene studies. For instance, our population was based in the United States and was made up of older adults, many of whom were in stable longterm relationships, whereas approximately half of the candidate gene studies utilized samples of adolescents from the Netherlands or Germany (Lucht et al, 2009;van Roekel et al, 2010van Roekel et al, , 2011van Roekel et al, , 2013Verhagen et al, 2014). Therefore, although our study benefited from a larger sample size than any of the previously reported candidate gene studies, we cannot discount the possibility that differences in the methodologies or the population under study led to our failure to replicate the previously published results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the studies in this table used environmental measures in addition to candidate genes, they are a subset of the studies in Table 3. Significant G × E findings were observed for four genes related to the HPA axis (the corticotropin releasing hormone receptor 1, or CRHR1, gene; Chou, Cacioppo, Kumari, & Song, 2014), the serotonin system (the serotonin transporter, or SLC6A4, gene; van Roekel, Scholte, Verhagen, Goossens, & Engels, 2010), the dopamine system (the dopamine receptor D2, or DRD2, gene; van Roekel, Goossens, Scholte, Engels, & Verhagen, 2011), and oxytocin (the OXTR gene; van Roekel, Verhagen, Scholte, et al, 2013). The observed pattern of results was in line with the general expectation in research on gene-environment interactions.…”
Section: Candidate Genesmentioning
confidence: 99%
“…The Netherlands DRD2 rs1800497 Parental support Significant; A2/A2 carriers with low support more lonely, but A2/A2 carriers with high support less lonely van Roekel, Verhagen, Engels, Goossens, and Scholte (2013) 302 Adolescents The Netherlands OXTR rs53576 Parental support Not significant van Roekel, Verhagen, Scholte, et al (2013) biological systems are involved, much like they do for GWAS, as described in the Molecular Genetics section.…”
Section: Gene Expressionmentioning
confidence: 99%